Exploring Human-Tech Hybridity at the Intersection of Extended Cognition and Distributed Agency: A Focus on Self-Tracking Devices - Duus, Rikke; Cooray, Mike; Page, Nadine C. (Frontiers in Psychology, 2018)
In an increasingly technology-textured environment, smart, intelligent and responsive technology has moved onto the body of many individuals. Mobile phones, smart watches and wearable activity trackers are just some of the technologies that are guiding, nudging, monitoring and reminding individuals in their day-to-day lives. These devices are designed to enhance and support their human users, however, there is a lack of attention to the unintended consequences, the technology non-neutrality and the darker sides of becoming human-tech hybrids. Using the extended mind theory and agential intra-action, we aim at exploring how human-technology hybrids gain collective skills and how these are put to use; how agency is expressed and how this affects the interactions; and what the darker sides are of being a human-technology hybrid. Using a qualitative method, we analyze the experiences of using a wearable activity tracker, with a specific focus on how the tracker and the individual solve tasks, share competences, develop new skills and negotiate for agency and autonomy. We contribute with new insight on human-tech hybridity and present a concept referred to as the agency pendulum, reflecting the dynamism of agency. Finally, we demonstrate how the extended mind theory and agential intra-action as a combined theoretical lens can be used to explore human-tech hybridity.